Chronic Administration of Anacetrapib Is Associated With Accumulation in Adipose and Slow Elimination. Issue 5 (2nd May 2017) - Krishna, R; Gheyas, F; Liu, Y; Hagen, DR; Walker, B; Chawla, A; Cote, J; Blaustein, RO; Gutstein, DE
Abstract : Anacetrapib is a novel cholesteryl‐ester transfer protein (CETP) inhibitor in late‐stage clinical development, shown in preceding clinical trials to have residual pharmacological activity after prolonged washout after chronic dosing. Preclinical findings suggest that white adipose tissue is a potential depot and that accumulation into adipose tissue governs the long‐term kinetics of anacetrapib in mice. A phase I study performed to test this hypothesis in humans revealed that plasma exposure was correlated with fat content in food administered with the drug. Plasma concentrations of anacetrapib seemed to reach plateau faster than adipose concentrations. Anacetrapib continued to accumulate in adipose during the treatment period despite apparent plateau in plasma with only minimal decline in adipose levels up to 1 year postdose. Because of its high lipophilicity, anacetrapib partitions into adipose tissue, this likely forms a drug reservoir that, in turn, contributes to the long residence time of the drug in plasma.